Formation and Evolution of the Corrosion Scales on Super 13Cr Stainless Steel in a Formate Completion Fluid With Aggressive Substances - Yue, Xiaoqi; Huang, Luyao; Qu, Zhihao; Yang, Zhile; Zhang, Lei; Hua, Yong (Frontiers in Materials, 2022)
The formation and evolution of the corrosion scales on super 13Cr stainless steel (SS) surface after exposure in a formate completion fluid with the presence of various aggressive substances was investigated by a combination of surface characterization techniques such as SEM/EDS, XRD and Raman spectra. The results indicate that the formation of Fe3O4 covered on the surface of super 13Cr SS as the inner layer accompanied with outer scattered FeS. The corrosion rate was below 0.07 mm/a after 120 hours of exposure in the formate fluid at 180°C under N2 environments; the presence of aggressive substances such as sulfide and CO2 in the formate fluid promoted the proceeding of anodic dissolution in the early period, the ingress of CO2 progressively increased the general corrosion rate to 1.7 mm/a. For CO2-containing conditions, the formation of FeCr2O4 and Cr(OH)3 were detected in the inner corrosion product layers and the precipitation of “sheet” shaped iron carbonate (FeCO3) was detected as the outer layer. The results suggested that the outer corrosion product layer provides less protective capability against corrosion than the inner layers, based on its incompact distribution and observed gaps between crystals via SEM observations.